2016
DOI: 10.1007/s40596-016-0590-3
|View full text |Cite
|
Sign up to set email alerts
|

Taking Care of Our Own: A Multispecialty Study of Resident and Program Director Perspectives on Contributors to Burnout and Potential Interventions

Abstract: Resident distress is common and most likely due to work-life imbalance and feeling unappreciated. However, residents are reluctant to seek help. Interventions that address work-life balance and increase access to support are urgently needed in academic medical centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 29 publications
2
72
1
Order By: Relevance
“…With a response rate of 61%, the e-mail survey of Holmes et al found a burnout rate of 69% (according to the Maslach burnout inventory) in over 300 residents across multiple specialties [4]. Of interest, the training directors in the study underestimated burnout rates among their residents.…”
mentioning
confidence: 90%
“…With a response rate of 61%, the e-mail survey of Holmes et al found a burnout rate of 69% (according to the Maslach burnout inventory) in over 300 residents across multiple specialties [4]. Of interest, the training directors in the study underestimated burnout rates among their residents.…”
mentioning
confidence: 90%
“…2 When we specifically examine the specialty of pathology, most recent estimates of burnout range from 46% to 52%, and rates of depression are estimated at 23%. 2,3 Although the rate of burnout for pathology is typically lower than that for other specialties, it still beckons the question of why one-half of pathologists are experiencing burnout? In this brief piece, the authors-as mental health experts-explore some specific sources of stress that are unique to the specialty of pathology and interventions that can be applied at the individual and programmatic levels to enhance the mental and physical well-being of residents and fellows.…”
Section: Unique Barriers To Well-being For Pathology Residents and Homentioning
confidence: 99%
“…In interviews with colleagues possible reasons given were a lack of information and motivation to participate in scientific work due to a perceived lack of benefit for the resident. Given an increased emphasis on the importance of work-life balance in recent years [7], we hypothesize that the motivation to do extra work above the required clinical duties is a key factor influencing the recruitment rate, and thereby influences the success of completing prospective clinical trials, especially in hospitals without a strong scientific infrastructure.…”
Section: Introductionmentioning
confidence: 99%